Effectiveness of Dasa Wisma Cadre Training on the Knowledge and Skills of Accompanying Families for the Prevention of Chronic Kidney Disease - Diyono, Diyono; Hartono, Hartono; Anantanyu, Sapja; Lestari, Anik (Global Health Science Group, 2024)
The prevalence of Chronic Kidney Disease in Indonesia increased from 0.2% in 2013 to 0.38% in 2018. The main risk factor for Chronic Kidney Disease is hypertension, which requires long-term treatment in the community. It is hoped that Dasa Wisma as social capital in society can vital role in preventing chronic kidney disease, so training for Dasa Wisma cadres is needed.Objective: To identify the effectiveness of Dasa Wisma cadre training on knowledge and skills in assisting family in the prevention of Chronic Kidney Disease in hypertension patientsMethods :Quasi-experimental research with a pre-post approach without control. Carried out on 25 Dasa Wisma cadres in the Surakarta City Health Service area. Samples were taken using multi-stage random sampling. Data was taken using knowledge tests and mentoring skills checklists. Data analysis used the Wilcoxon test.Results:There is a difference in knowledge scores before training (mean=67.73±12.57; med 50th=66.67) and after training (mean=79.47±14.77; med 50th=80.00), Wilcoxon test results z=-2.97;p=0.003 and mentoring skills value before training (mean=91.73±12.36; med 50th=100) and after training (mean=97.87±4.60; med 50th=100), Wilcoxon test results z=-2.26;p=0.024 Conclusions: Cadre Training effective to increase cadres' knowledge and skills in providing assistance to prevent chronic kidney disease.